On the application of RRSS motion generation and RRSS Axode generation for the design of a concept prosthetic knee. Issue 3 (3rd July 2017) - D'Alessio, Jerry; Russell, Kevin; Lee, Wen-Tzong; Sodhi, Raj S.
ABSTRACT: In this work, equation systems for RRSS motion generation and RRSS axode generation are applied to produce a concept above the transfemoral amputation prosthetic knee. First, an RRSS linkage is synthesized to approximate a series of tibial positions during knee flexion. Next, the fixed and moving axodes of the synthesized RRSS linkage are generated. Because the coupler motion of an RRSS linkage can be replicated by rolling its moving axode over its fixed axode, the axodes for the synthesized RRSS linkage are incorporated as gears to produce a concept prosthetic knee. The resulting prosthetic knee approximates the natural spatial motion of the tibia during knee flexion and extension (unlike prosthetic knee designs that include simple pin joints).